The worlds of medieval Europe - Backman, Clifford R. (Oxford University Press, 2003)
This work updates and revises the traditional representations of the Middle Ages. The traditional focus on the political affairs of Northern Europe is balanced by attention to medieval society as it developed in the Mediterranean. The author integrates Islamic and Byzantine history into the narrative.